Co-design and implementation of Index Based Flood Insurance (IBFI) in flood proofing communities of Mazabuka District, southern Zambia - Umer, Yakob; Makungwe, Mirriam; Amarnath, Giriraj; Jacobs-Mata, Inga; Banda, N.; Njoroge, M. (International Water Management Institute (IWMI), 2024)
The Magoye River, a vital resource for communities in Zambia's Southern Province, has a history of seasonal flooding with severe consequences. During the rainy season, the river often overflows, inundating surrounding areas and causing widespread crop and infrastructure damages. Factors such as deforestation and climate change exacerbate this natural phenomenon, leading to loss of lives, displacement, and destruction of infrastructure, farmlands, and livelihoods. An innovative insurance solution has been developed to address these challenges, compensating affected communities for losses incurred during flood events. The CGIAR Initiative on Diversification in East and Southern Africa, Ukama-Ustawi (UU), identified the bundling of climate insurance as an innovative climate risk management solution for smallholder farmers in Southern and Eastern Africa. This innovation involved mapping flood-prone agricultural areas near the river, ensuring tailored support for those most vulnerable. The innovation was aimed to mitigate the financial risks associated with recurrent flooding by providing timely insurance payouts to farmers while promoting climate resilience.